2012
DOI: 10.1007/s10865-012-9441-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging study reveals differences in the habituation to psychological stress in patients with Crohn’s disease versus healthy controls

Abstract: In patients with Crohn's disease (CD) stress is believed to increase the incidence of disease relapse. The brain processes stressful stimuli and triggers the stress-evoked responses. Habituation to stress is an adaptive process that allows minimizing these responses. We hypothesized inadequate habituation to stress in CD patients. The aim of this study was to compare the neural habituation between CD patients and controls. Twenty CD patients and eighteen controls underwent a functional magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…These results also indicate decreased coupling between the cortex and subcortical regions and were consistent with the imaging results in this study. A previous study also showed that CD patients have abnormal neural activity in the amygdala, hippocampus, insula, putamen, cerebellar regions when performing stress-evoking tasks, suggesting altered habituation to stress in these patients32. Structurally, CD patients were found to exhibit decreased GM volumes in the frontal and the anterior midcingulate cortex17.…”
Section: Discussionmentioning
confidence: 89%
“…These results also indicate decreased coupling between the cortex and subcortical regions and were consistent with the imaging results in this study. A previous study also showed that CD patients have abnormal neural activity in the amygdala, hippocampus, insula, putamen, cerebellar regions when performing stress-evoking tasks, suggesting altered habituation to stress in these patients32. Structurally, CD patients were found to exhibit decreased GM volumes in the frontal and the anterior midcingulate cortex17.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies show alternations in gray matter (GM) structures including GM volumes and cortical thickness in multiple brain regions of CD patients, which in certain brain regions are correlated with disease duration [1, 6]. CD patients also have been found to exhibit altered habituation to stress and altered neural activity in the amygdala, hippocampus, insula, putamen, and cerebellar regions when performing stress-evoking tasks [2]. However, to date, there has been no study on resting-state brain activity in CD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Rs-fMRI analytical methods include regional homogeneity (ReHo)[34], functional connectivity (FC)[35] and amplitude of low-frequency fluctuation (ALFF)[36]. Using fMRI, Agostini et al[37] and Bao et al[38] found abnormal functional activity in the cerebral cortex of patients with CD (Table 1). …”
Section: Bold-fmri For Detecton Of Brain Changes In CDmentioning
confidence: 99%
“…Agostini et al[37] hypothesized inadequate habituation to stress as a characteristic for CD patients, and their study sought to compare neural habituation between CD patients and healthy subjects. During a high-stress task, different neural regions were activated between the two groups.…”
Section: Bold-fmri For Detecton Of Brain Changes In CDmentioning
confidence: 99%
See 1 more Smart Citation